2022
DOI: 10.3390/cancers14122983
|View full text |Cite
|
Sign up to set email alerts
|

α-Ketoglutarate-Mediated DNA Demethylation Sustains T-Acute Lymphoblastic Leukemia upon TCA Cycle Targeting

Abstract: Despite the development of metabolism-based therapy for a variety of malignancies, resistance to single-agent treatment is common due to the metabolic plasticity of cancer cells. Improved understanding of how malignant cells rewire metabolic pathways can guide the rational selection of combination therapy to circumvent drug resistance. Here, we show that human T-ALL cells shift their metabolism from oxidative decarboxylation to reductive carboxylation when the TCA cycle is disrupted. The α-ketoglutarate dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This resulted in sPD hNPCs in an efflux of carbon out of the citric acid cycle at the level of α-ketoglutarate, diminishing the production of reducing equivalents. This is in line with metabolomic flux analysis that revealed enhanced reductive carboxylation upon genetic deletion of OGDHC subunits 64 . Thus overall, the alterations in OGDHC activity seemed to introduce an sPD-specific state of hypometabolism marked by reduced glucose and glutamine metabolization, a reduced mitochondrial ATP production rate, as well as a reduced abundance of most quantified metabolites.…”
Section: Discussionsupporting
confidence: 84%
“…This resulted in sPD hNPCs in an efflux of carbon out of the citric acid cycle at the level of α-ketoglutarate, diminishing the production of reducing equivalents. This is in line with metabolomic flux analysis that revealed enhanced reductive carboxylation upon genetic deletion of OGDHC subunits 64 . Thus overall, the alterations in OGDHC activity seemed to introduce an sPD-specific state of hypometabolism marked by reduced glucose and glutamine metabolization, a reduced mitochondrial ATP production rate, as well as a reduced abundance of most quantified metabolites.…”
Section: Discussionsupporting
confidence: 84%
“…Strikingly, the combination treatment of enzalutamide and the TET2 inhibitor, Bobcat339 [56][57][58][59][60][61][62][63] , significantly impaired the growth of enzalutamide-resistant ZNF397-KO cells, as demonstrated in an in vitro cell viability assay (Fig. 6F).…”
Section: Targeting Tet2-driven Epigenetic Rewiring Represents a Novel...mentioning
confidence: 86%
“…Consistent with other studies [ 35 ], our analysis indicated that PDHA1 is an independent prognostic factor for OS and has a positive correlation with histological type and tumor size. Finally, DLST is closely involved in cell metabolism, contributing to the transduction of α-ketoglutarate into succinyl-CoA10 in the TCA cycle in an irreversible manner [ 36 ]. In several cancer types, DLST is found to be negatively correlated with clinical outcomes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%